2012
DOI: 10.4236/fns.2012.311203
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Dietary Practices during School Day in Jeddah, Western Saudi Arabia

Abstract: The schools teachers dietary practices during the school day should reflect a healthy dietary pattern both in quality and quantity of foods consumed particularly in countries that witness an epidemic of obesity related Type-2 diabetes mellitus. The objective of this study was to identify the local dietary practices of the schools teachers in Jeddah, western Saudi Arabia. A Cross-section observational study using a pre-designed questionnaire to identify the local pattern of dietary practices during school day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among individuals, including schoolteachers, the obesity risk increases with the degree of physical inactivity, sedentary life, and dietary behaviour ( 17 ). The prevalence of obesity among schoolteachers was 30% in a Brazilian study ( 18 ) and 40% in a Saudi study in Jeddah ( 19 ). Obesity is associated with lifestyle and comorbidities among public school teachers ( 20 ).…”
Section: Introductionmentioning
confidence: 95%
“…Among individuals, including schoolteachers, the obesity risk increases with the degree of physical inactivity, sedentary life, and dietary behaviour ( 17 ). The prevalence of obesity among schoolteachers was 30% in a Brazilian study ( 18 ) and 40% in a Saudi study in Jeddah ( 19 ). Obesity is associated with lifestyle and comorbidities among public school teachers ( 20 ).…”
Section: Introductionmentioning
confidence: 95%
“…Most teachers reported high-fat intakes and frequently purchased sweetened soft drinks and high-fat or high-sugar snack foods from school vending machines. A recent observational study of 140 teachers' dietary practices during the school day in Western Saudi Arabia concluded that positive teacher role modeling is necessary in reducing poor dietary behaviors and outcomes among children [20]. Arcan et al [21] studied classroom food practices and food-related beliefs of 75 kindergarten and first grade teachers on a large American Indian reservation.…”
Section: Introductionmentioning
confidence: 99%